Acute HIV at the Time of Initiation of Pre-exposure or Post-exposure Prophylaxis: Impact on Drug Resistance and Clinical Outcomes. (1st June 2021) - Johnson, Kelly A.; Chen, Miao-Jung; Kohn, Robert; Sachdev, Darpun; Bacon, Oliver; Lee, Sulggi; Cohen, Stephanie E.
Abstract : Background: Initiating pre-exposure or post-exposure prophylaxis (PrEP/PEP) in the setting of undiagnosed acute HIV (AHI) could cause antiretroviral resistance. We sought to characterize clinical outcomes and drug resistance mutations among individuals prescribed PrEP/PEP with undiagnosed AHI at a San Francisco sexually transmitted disease clinic. Setting: In our PrEP/PEP program, patients are tested for HIV using a point-of-care antibody test. If negative, patients are started on prophylaxis and screened for AHI using pooled HIV RNA (5–10 days turn-around). We used 2-drug PEP until 05/2016. Methods: We identified patients who had as-yet-undiagnosed AHI on the day of PrEP/PEP start between 2011 and 2018, then used our clinical record and surveillance data to describe HIV resistance and clinical outcomes. Results: Of 1758 PrEP and 2242 PEP starts, there were 7 AHI cases among PrEP users (0.40%) and 6 among PEP users (0.30%). Median times for linkage to HIV care, initiation of HIV treatment, and viral suppression were 7, 12, and 43 days. On initiation of HIV care, 3 patients (23%) were found to have an M184 mutation 7–12 days after starting PrEP/PEP. All 3 had genotyping performed on stored serum available from the date of PrEP/PEP start, each of which demonstrated wild-type virus. All 3 patients achieved durable viral suppression. Conclusions: Although rare (occurring <0.5% of the time), AHI in the setting of PrEP/2-drug PEP can result in an M184 within days. Even with M184, persons with AHI achieve viral suppression when rapidly linked to care and initiated on antiretroviral therapy. Providers should consider AHI screening when starting PrEP/PEP.